Id-ul-Fitr - Pirotta, Saviour (London : Wayland, 2006)
Photographs and simple text describe the Muslim holiday of Id-ul-Fitr, a celebration to mark the end of Ramadan.
Includes index.
3.5
K-3.
K-3
Keywords: Fasts and feasts -- Islam -- Juvenile literature; Ramadan -- Juvenile literature; v; Fasts and feasts; Ramadan; 9; Islamic holidays; Ramadan; 2